FEMALE EMIGRATION IN THE BRITISH EMPIRE IN THE LATE XIXTH AND EARLY XXTH CENTURIES IN ASSESSMENTS OF MODERN RESEARCHERS - Kryuchkova, Natalya Dmitrievna (Közép-Európai Közlemények, 2020)
This paper is aimed to consider the issue of the intra-imperial emigration of single British women in the late 19th – early 20th centuries in gender and imperial studies. The views of contemporary scholars on various aspects of female emigration movement such as the ideology of female emigration, the functions of women as “builders of the Empire”, the organizations and organizers of emigration, the influence of the female emigration movement on the British society are presented in the article. The author concludes that almost all researchers recognized the importance of female emigration as the essential component of the imperial project aimed at strengthening ties with settlement colonies, and at the same time its role in widening the limits of “women`s sphere”, and in providing new opportunities for female self-realization. The article outlines the directions for future researches of the problem of female emigration in the 19th-20th centuries.